Shared bias in H chain V-J pairing in naive and memory B cells - Levi, Reut; Dvorkin, Shirit; Louzoun, Yoram (Frontiers in Immunology, 2023)
H chain rearrangement in B cells is a two-step process where first DH binds JH , and only then VH is joined to the complex. As such, there is no direct rearrangement between VH and JH . Nevertheless, we here show that the VH JH combinations frequency in humans deviates from the one expected based on each gene usage frequency. This bias is observed mainly in functional rearrangements, and much less in out-of-frame rearrangements. The bias cannot be explained by preferred binding for DH genes or a preferred reading frame. Preferred VH JH combinations are shared between donors, suggesting a common structural mechanism for these biases. Through development, the preferred VH JH combinations evolve during peripheral selection to become stronger, but less shared. These results suggest that peripheral Heavy chain VH JH usage is initially shaped by a structural selection before the naive B cell state, followed by pathogen-induced selection for host specific VH − JH pairs.